Effectiveness of integrated nutrient management on growth and yield parameters of okra (Abelmoschus esculentus L.) (Asian-Australasian Journal of Food Safety and Security, 2020)
Integrated use of organic and inorganic fertilizers could improve both growth and yield of okra plant. The present study was carried out to evaluate the effect of organic and inorganic fertilizer on growth and yield parameters of okra (Abelmoschus esculentus L.) at experimental area of Noakhali Science and Technology University, Bangladesh during the period of 18th December, 2018 to 19th March, 2019 (Rabi season). In this experiment, “Arka Anamika” variety of okra was used. The experiment was laid out in Randomized Complete Block Design (RCBD) with four treatments viz. T1= INM (organic and inorganic), T2= Inorganic (NPK), T3= Organic (cowdung), T4= Control and three replications. Data were taken on the growth and yield parameters such as plant height (cm), number of leaves per plant, number of branches per plant, days to first flowering (days), number of fruit per plant, individual fruit weight (gm), fruit length (cm) and fruit diameter (cm). Among all treatments INM (organic and inorganic) was responsible for highest plant height (49.96 cm), maximum number of leaves per plant (22.33) and branches per plant (6.33), accelerated days to first flowering (39 days), increases the number of fruit per plant (14.33), individual fruit weight (24.89 gm), fruit length (15.5 cm) and fruit diameter (1.98 cm). So this study clearly indicated that, among all treatments INM (Organic and inorganic) performed the best and it will be suitable for okra production.Asian Australas. J. Food Saf. Secur. 2020, 4 (2), 41-48